Plasma von Willebrand factor level as a prognostic indicator of patients with metastatic colorectal carcinoma - Wang, Wei-Shu (World J Gastroenterol, 2005)
AIM: To evaluate the correlations of plasma von Willebrand factor (vWF) level with the distant metastasis and prognosis of patients with colorectal cancer. METHODS: A total of 86 patients with histologically confirmed metastatic colorectal cancers receiving treatment at Taipei Veterans General Hospital were enrolled. All patients had measurable metastatic lesions and life expectancies of more than 3 mo. Plasma vWF levels were measured by immuno-turbidimetric assay and compared with results from 40 non-metastatic colorectal cancer patients and 22 healthy controls. Patients with metastatic colorectal cancer were divided into two groups according to serum vWF levels and the differences between these two groups were analyzed using χ(2) test. Data on age, gender, performance status, location of primary tumor, extent of metastasis, site of metastases, histological differentiation, serum CEA and plasma vWF levels were analyzed to determine association with survival. Survival curves were constructed by Kaplan-Meier product limit method and the data was analyzed using log-rank test on a microcomputer. Multivariate analysis using the Cox’s proportional hazards regression model was then performed to determine the independent prognostic indicators among all of the possible variables. RESULTS: Colorectal cancer patients were identified as having significantly higher plasma vWF concentrations than healthy controls (P<0.05). Moreover, higher vWF plasma levels were associated with advanced tumor stage (P<0.05) and the presence of multiple metastases (P = 0.014). Patients with lower vWF plasma levels (≤160%) survived significantly longer than those with a higher plasma vWF level (log-rank test, P = 0.0043). By multivariate analysis, plasma vWF levels (P<0.001), the extent of metastasis (P = 0.012), and the performance status (P = 0.014) were identified as independent prognostic factors. CONCLUSION: Our data indicates that high plasma vWF concentrations correlate with advanced diseases and significantly poor prognosis of patients with metastatic colorectal carcinoma. It may serve as a potential biological marker of disease progression in these patients.